1993
DOI: 10.1037/0021-9010.78.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Nature and consequences of halo error: A critical analysis.

Abstract: The definition of halo error that dominated researchers' thinking for most of this century implied that (a) halo error was common; (b) it was a rater error, with true and illusory components; (c) it led to inflated correlations among rating dimensions and was due to the influence of a general evaluation on specific judgments; and (d) it had negative consequences and should be avoided or removed. We review research showing that all of the major elements of this conception of halo are either wrong or problematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(202 citation statements)
references
References 65 publications
1
181
0
9
Order By: Relevance
“…Earlier, we noted that one popular form or training instructed raters not to make halo errors, not to be lenient, and so forth. It is not clear that removing halo, leniency, and the like makes g e t t i ng r i d of pe r f or m a nc e r at i ng s performance ratings better measures of performance, and it is even plausible that efforts to suppress these so-called errors make performance ratings worse (Murphy, 1982;Murphy, Jako, & Anhalt, 1993). Borman (1977) argued that under some circumstances, it might be possible to assess the accuracy of performance ratings.…”
Section: Weak Criteria For Evaluating Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we noted that one popular form or training instructed raters not to make halo errors, not to be lenient, and so forth. It is not clear that removing halo, leniency, and the like makes g e t t i ng r i d of pe r f or m a nc e r at i ng s performance ratings better measures of performance, and it is even plausible that efforts to suppress these so-called errors make performance ratings worse (Murphy, 1982;Murphy, Jako, & Anhalt, 1993). Borman (1977) argued that under some circumstances, it might be possible to assess the accuracy of performance ratings.…”
Section: Weak Criteria For Evaluating Ratingsmentioning
confidence: 99%
“…Other rater errors, including leniency or severity and range restriction, were soon identified. There is a substantial research literature that analyzes rater error measures, particularly measures of halo (Balzer & Sulsky, 1992;Cooper, 1981aCooper, , 1981bMurphy, 1982;Murphy & Anhalt, 1992;Murphy & Balzer, 1989;Murphy, Jako, & Anhalt, 1993;Nathan & Tippins, 1989;Pulakos, Schmitt, & Ostroff, 1986). On the whole, rater error measures are deeply flawed criteria.…”
Section: Weak Criteria For Evaluating Ratingsmentioning
confidence: 99%
“…Based on this risk assessment, auditors plan and execute audit procedures. However, research in psychology and on performance evaluations has demonstrated that evaluative judgments based on holistic characteristics can create a halo effect that influences subsequent judgments about detailed performance measures, even when the holistic judgment is not related to the evaluation of the detailed metrics (Nisbett and Wilson 1977;Murphy et al 1993). For example, research has shown that rendering a favorable holistic evaluation can cause an individual to provide a positive assessment for information related to detailed performance measures, even when the detailed performance measures may convey less than positive information (Finucane et al 2000).…”
Section: Multiple Audit Tasks For the Same Clientmentioning
confidence: 99%
“…Recent research in psychology has contributed to reducing the concern about this so-called "halo effect" (Balzer and Sulsky, 1992;Murphy et al 1993). Nevertheless, if there is agreement among team members that a given project was a failure, it is reasonable to argue that there is a risk that the retrospective account of how the project unfolded will be colored by this view.…”
Section: Data Analysis and Measuresmentioning
confidence: 99%